THE ROLE OF ROAD TRAFFIC AND TRANSPORTATION FORUM IN THE REGIONAL ROAD GRANTS PROGRAM - Dewi Atikah (Journal Innovation of Civil Engineering (JICE), 2020)
The Road Traffic and Transportation Forum (FLLAJ) is a prerequisite for the Regional Road Grant Program to increase community involvement and transparency of the quality of road maintenance work, through cooperation and participation of all stakeholders. FLLAJ's duties include receiving input or complaints from the public regarding roads, traffic and road transport. The purpose of writing this paper is to determine the number of community complaints that have been submitted through the FLLAJ website and whether the problems with these complaints can be resolved. The problem limitation in this study is the Provincial FLLAJ, namely the Bangka Belitung Islands Province, West Nusa Tenggara Province, and East Java Provinces. Complaints that are entered through the respective FLLAJ's website, not through other social media which cannot be accessed by the public freely. The method used in this analysis is descriptive method. The result of this analysis is that the most complaints came from West Nusa Tenggara Province with a total of 81 complaints. As stated on the website, no one has uploaded any follow-up on these complaints, so for the second problem, it cannot be analyzed whether the problem has been can be resolved or not, because there is no detailed information regarding the resolution of the complaint. In conclusion, the FLLAJ plays a role in the Regional Road Grant Program, with many complaints being made on the FLLAJ websites of each province.